Workplace in the new paradigm : alternative officing - Wahab, Ahmad Fauzi (Universiti Teknologi Malaysia, 1999)
Altemative o.tficing is a collective terminology used to explain d([ferent strategfes which hcIue changed the design of workplace and how people work. Economical and societal forca ..... cIriueR organisations to analyse the processes in which people work. As a result, .tra~hcIue ... cIeueIoped that maximise space usage based on amount of time workers spend UuIfck and outlide the oJ1ke and each other. This allows the organisation to save space and inctWaee productiPity. This paper discusses workplace in the changing environment and the I1CUioua strategf.es of alternative o.tficing such as telecommuting, just-in-time o.tfice, non-territorial spaces, landing sites, caves and commons, and thefree address space